2007
DOI: 10.1080/09670260601159346
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of formation and secretion of heterococcoliths byCoccolithus pelagicusssp.braarudii

Abstract: The formation and secretion of heterococcoliths by the non-motile life phase of the coccolithophore Coccolithus pelagicus was investigated using electron microscopy and time-lapse bright field imaging. Coccolithogenesis in C. pelagicus exhibited sequential mineralization of single coccoliths in Golgi-derived and nuclear-associated vesicles, a pattern similar to the formation of heterococcoliths in Emiliania huxleyi. Our TEM data show that only on maturation does the single coccolith vesicle migrate away from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 49 publications
4
100
1
Order By: Relevance
“…The exponential growth rate of subsp. braarudii was similar to those determined previously under similar experimental conditions (Taylor et al, 2007;Buitenhuis et al, 2008). Although other studies have observed higher exponential growth rates (up to 0.9 d −1 ) for the same strain (Langer et al, 2006;Krug et al, 2011), these authors used a higher irradiance and a longer light phase which probably increased cell division rates.…”
Section: Effect Of Phosphorus Limitation and Temperature On Culture Gsupporting
confidence: 69%
“…The exponential growth rate of subsp. braarudii was similar to those determined previously under similar experimental conditions (Taylor et al, 2007;Buitenhuis et al, 2008). Although other studies have observed higher exponential growth rates (up to 0.9 d −1 ) for the same strain (Langer et al, 2006;Krug et al, 2011), these authors used a higher irradiance and a longer light phase which probably increased cell division rates.…”
Section: Effect Of Phosphorus Limitation and Temperature On Culture Gsupporting
confidence: 69%
“…In Emiliania huxleyi, Ca 2+ is thought to cross the plasma membrane through channels following its electrochemical gradient, then being transported into the endoplasmic reticulum and calcification vesicle potentially by ATP-dependent pumps or ion exchangers (possibly with H + ) and Ca 2+ -ATPase, respectively (Mackinder et al 2011). The rapid increase in inorganic carbon fixation already after 10 min could be linked to an increased calcification rate together with faster exudation of coccoliths (E. huxleyi produces about 1 coccolith h −1 , Paasche 2001) similarly to Coccolithus pelagicus (Taylor et al 2007). …”
Section: Phaeodactylum Tricornutummentioning
confidence: 99%
“…Thus far, relatively common fossil coccospheres have been documented from at least 24 localities (Burns, 1975;Covington, 1985;Lambert, 1987;Young and Bown, 1991;Mai, 1997;Mai et al, 1998;Henderiks, 2008;Ciurej, 2010;Bown et al, 2014) representing low to high latitudes, the North and South Atlantic oceans, the North Pacific Ocean, the Indian Ocean and Southern Ocean, and ranging from Kimmeridgian (Late Jurassic) to Pleistocene. Coccosphere geometry analysis is therefore likely to prove applicable at a range of localities and time intervals, but reasoned selection of sampling sections is likely to be important for retrieving sufficient coccospheres for robust data analysis.…”
Section: Coccosphere Geometry As a Proxy For Growth Phase In The Fossmentioning
confidence: 99%
“…The relationship between growth phase, ∅ and C N can be understood by considering the process of cell division and how it is affected by the nutrient depletion that instigates non-exponential-phase growth. Both ∅ and C N vary as each cell progresses through the cell division cycle (unpublished observations; Taylor et al, 2007;MĂźller et al, 2008). Recently divided cells are small, with approximately the minimum number of coccoliths required to form a complete cell covering (unpublished observations; Fig.…”
Section: Physiological Insights Into Coccosphere Geometrymentioning
confidence: 99%